The T-form organization using technology to design organizations for the 21st century - Lucas, Henry C. (Jossey-Bass, 1996)
Although information technology (IT) has long been used to support existing organizational structures, dramatic developments in communication technology over the last decade have revolutionized the design of today's leading organizations. Using such examples as Frito-Lay, France Telecom, Baxter International, Merrill Lynch, and American Airlines, Henry C. Lucas, Jr., goes beyond mere description of networked organizations, virtual organizations, and similar "businesses of the future" to show how to use information technology - combined with conventional approaches to organization design - to create the technologically-based "T-Form" organization.
Keywords: Organisatieverandering; Prognoses; Strategisch management; Communication; Communication in organizations -- Technological innovations; Industrial organization -- Forecasting; Industry; Information technology; Organization and Administration -- trends; Reengineering (Management) -- Forecasting; Technology; Twenty-first century -- Forecasts; Managementinformationssystem